Different Understanding about the Other Shore: the Introspection Study on Chinese and Western Art under the Natural Disaster - Sun, Zhi-hao (Talenta Publisher, 2021)
No matter what the different cultural backgrounds are, they will always collide and generate divergence on the same point of intersection and then continue moving forward in the direction of collective cognition. At present, the global world is facing severe pestilence disasters; China Art Circle made many responses immediately at the beginning of the epidemic situation and tried to fight the epidemic situation, encourage the front-line medical staff and provide energy for them. However, when the epidemic situation in China trends to calm, the art theme about the epidemic situation also suddenly keeps silent. It looks like calm without great waves; however, through investigating Western art, it is found that the Western Art Circle has different orientations on the attitude to disasters; considering its inner core, it maps the further understanding of groups with different cultural backgrounds on the cognition of other shores of life- different life and death idea influence the social outlook, view of life and expectation of life fate of different groups. Meanwhile, they also promote the society to show different introspection paths while facing disasters. The study uses empirical analysis to identify and collect the image information from classical paintings of the East and the West. The results show that compared with Western art, Chinese art conveys a message that focuses more on maintaining the country's stability.